ANALISIS EFEKTIVITAS DAN EFISIENSI PELAPORAN TENAGA KERJA DENGAN MENGGUNAKAN SISTEM MANUAL DAN SISTEM ONLINE (STUDI KASUS BPJS KETENAGAKERJAAN CABANG GRESIK) - Sasongko Budi Laksono (Jurnal Manajerial, 2019)
This study aims to determine the effectiveness and efficiency of employment reporting in the office BPJS Employment Ketenagakerjaan Gresik. Using 6 informants from BPJS Ketenagakerjaan employee and 4 informants from the participant to know comparison of effectiveness and efficiency of reporting in BPJS Ketenagakerjaan of Gresik. The analysis was done by using constant comparative analysis technique. The results show that Online reporting application meets the indicators of effectiveness and efficiency.